Mutiple keratocystic odontogenic tumors (KCOT) in a patient with Gorlin syndrome: a case report with late presentation and absence of skin manifestations. (December 2016) - Hashmi, Atif; Edhi, Muhammad; Faridi, Naveen; Hosein, Mervyn; Khan, Mehmood
Abstract Background Gorlin syndrome is a rare autosomal dominant syndrome characterized by multiple basal cell carcinomas, keratocystic odontogenic tumors (KOT) and falx cerebral calcifications, which occur due to mutation in PTCH gene. Case presentation A 36 year old Asian patient presented with jaw swelling and pain. Radiographic examination revealed six cysts in maxilla and mandible which were excised and histologically were compatable with keratocystic odontogenic tumors. CT scan also revealed falx cerebral calcification which led to the diagnosis of Gorlin syndrome confirmed on genetic testing. There was no evidence of basal cell carcinoma and other manifestations of Gorlin syndrome were absent. Conclusions Multiple KCOT are hallmark of Gorlin syndrome and should always leads to its suspicion even in the absence of other manifestations and late presentation. Moreover, keratocystic odontogenic tumors have a particularly higher risk of recurrence and patients with Gorlin syndrome are prone to develop additional keratocystic odontogenic tumors from basal cells of oral epithelium. Therefore we suggest a stepwise approach to manage such patients which include a preoperative biopsy to establish a definitive diagnosis and complete removal of all keratocystic odontogenic tumors to prevent recurrence followed by close clinical follow up and early removal of any newly developed or recurrent cyst. Additionally thorough clinical examination is necessary to rule out the possibility of Gorlin syndrome in any patient with keratocystic odontogenic tumors as there are only subtle differences in histology of those cysts with a syndromic association and clinical features of Gorlin syndrome are markedly variable. Hence late occurrence of keratocystic odontogenic tumors and absence of skin manifestations like basal cell carcinoma should not preclude a diagnosis of Gorlin syndrome.